2000
DOI: 10.1091/mbc.11.2.555
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bone Morphogenetic Protein-responsive Smad-binding Element

Abstract: Bone morphogenetic proteins (BMPs) are pleiotropic growth and differentiation factors belonging to the transforming growth factor-β (TGF-β) superfamily. Signals of the TGF-β-like ligands are propagated to the nucleus through specific interaction of transmembrane serine/threonine kinase receptors and Smad proteins. GCCGnCGC has been suggested as a consensus binding sequence for DrosophilaMad regulated by a BMP-like ligand, Decapentaplegic. Smad1 is one of the mammalian Smads activated by BMPs. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 44 publications
(78 reference statements)
3
148
0
4
Order By: Relevance
“…An important indication deduced from these observations is that the DNA binding af®nity of Smads alone may be relatively low. We found that mammalian Smad1 binds to the Mad consensus binding site found in Ubx and labial (Kusanagi et al 2000). However, the sequence speci®city for Smad1 binding was not very rigid.…”
Section: Discussionmentioning
confidence: 80%
“…An important indication deduced from these observations is that the DNA binding af®nity of Smads alone may be relatively low. We found that mammalian Smad1 binds to the Mad consensus binding site found in Ubx and labial (Kusanagi et al 2000). However, the sequence speci®city for Smad1 binding was not very rigid.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, Smad1 and Smad2 associate with different transcription factors, bind distinct DNA sequences and regulate distinct pools of genes. 41,44 Of course, We observed that an anti-TGFbRII Ab efficiently blocked Smad1 phosphorylation as well as the formation of Smad1/ Smad4 complexes. This supports participation of TGFbRII in the data 8).…”
Section: Tgfb-mediatedmentioning
confidence: 72%
“…Smad1/Smad4 complexes are required for DNA binding or regulation of gene transcription by Smad1. 41 Their presence further demonstrates that the phosphorylation of Smad1 observed here activates the protein, in contrast to a phosphorylation targeting its linker domain and preventing its nuclear translocation. 42 TGFb induced not only Smad1 but also Smad2 phosphorylation in H2 cells.…”
Section: Tgfb-mediatedmentioning
confidence: 73%
“…Interestingly, Smad2 has 30-amino acid insertion immediately prior to the DNA-binding b-hairpin, which inhibits the capacity of Smad2 to bind to DNA (Shi et al, 1998;Dennler et al, 1999;Yagi et al, 1999). BMP RSmads (and also Smad3 and Smad4) have also been shown to bind to GC-rich sequence motifs (Kim et al, 1997;Labbe  et al, 1998;Ishida et al, 2000;Kusanagi et al, 2000), suggesting that DNA binding speci®city of Smads is not so strict (Qing et al, 2000). GC-rich sequences have been found to be critically important for BMP-induced activation of Smad6 (Ishida et al, 2000).…”
Section: Transcriptional Control By Smadsmentioning
confidence: 99%